Estimating Facility‐Level Monthly Water Consumption of Commercial, Industrial, Municipal, and Thermoelectric Users in Virginia. (16th June 2022) - McCarthy, Morgan; Brogan, Connor; Shortridge, Julie; Burgholzer, Robert; Kleiner, Joseph; Scott, Durelle
ABSTRACT: Understanding water consumption is an important component of water management. However, water consumption data are limited and consumption coefficients do not account for variability through time and across users. This study combines federally maintained discharge data with state‐maintained withdrawal data at monthly time steps to estimate facility‐level and spatially aggregated water consumption in Virginia between 2010 and 2016. We evaluate (1) the feasibility of using discharge and withdrawal datasets to estimate sub‐annual water consumption, (2) how these consumption estimates vary depending on the level of spatial aggregation, and (3) what patterns of seasonality exist in consumption estimates. We find that a combined process of text matching and geospatial analysis is effective in matching facilities and yielding monthly time‐series of water consumption. Our results suggest that median consumption in industrial (17%) and commercial (19%) facilities may be higher than median consumption coefficients in the literature (10%). Consumption estimates also demonstrated more variability across facilities and seasons than aggregate coefficients in the literature suggest. Combining this approach with institutional knowledge can assist in quantifying issues such as inter‐basin transfers and infiltration that impact consumption estimates, ultimately allowing for more accurate accounts of water use and availability.